SYSTEMIC FAMILY THERAPY WORKING WITH DRUG USERS (Annual of the Faculty of Philosophy in Skopje, 2020)
After years of medical research, it is clear that drug addiction is a complex multifactorialbiological and behavioural disorder. Scientific advances have made it possibleto develop treatments that help normalize the functioning of the brain of those affectedand support them in changing their behaviour. Providing evidence-based treatmentsnow helps millions of people regain control of their lives. It is the psychosocial workwith these people that provides such methods that in cooperation with the addict, whomust be prepared for this type of cooperation, can produce positive effects for him andthe environment, including the family that is always most affected by the addictiveproblem.This paper deals with some of those methods, that is, systemic family therapythat would enable progress in the addict's behaviour, his/her desire to change behaviouror treatments for relapse and prevention of relapse and recurrent behaviour. All thiscomposition of psychosocial work, work through family therapies, and control over theaddict enabled and assisted by official health and civic associations contribute to theformation of an overall strategy to help addicts and reduce the number of addicts in thecountry.
Keywords: SYSTEMIC FAMILY THERAPY; TREATMENT; ADDICTS